Person-centered care, shared decision-making, and service modularity in colorectal cancer treatment: A mixed-method study of patient and professional perspectives - Mayke de Klerk; Evita A. Bartels; Janine Timmers; Lenny M. W. Nahar-van Venrooij; Angèle P. M. Kerckhoffs; Esther de Vries; Bert R. Meijboom (PLoS ONE, 2026)
Background Cancer care pathways improve outcomes through standardization but often lack flexibility to address individual needs. In this case study, we applied a composite model to examine its applicability by studying how person-centered care, shared decision-making, and service modularity are enacted within the colorectal cancer pathway of a large Dutch teaching hospital. Methods We conducted a cross-sectional mixed-method single case study. Patients completed questionnaires on health-related well-being and colorectal cancer care experiences. We explored person-centered care, shared decision-making, and service modularity and their interaction using questionnaires (patients) and semi-structured interviews (patients and healthcare professionals). Quantitative data were analyzed with descriptive statistics; qualitative data were analyzed thematically. Results Our findings showed gaps between formal structures and actual delivered care, especially in how shared decision-making and service modularity work together to provide person-centered care. Healthcare professionals’ limited modular thinking restricted customization. Information was delivered mainly according to protocols and did not fully address individual preferences, while preference elicitation was inconsistent. Care packages tended to follow clinical routines rather than reflect true patient priorities. Coordination was generally sufficient but revealed weaknesses during care transitions. Conclusion The composite model provides a practical framework to enhance person-centered cancer care by revealing structural barriers to shared decision-making and customization. Promoting modular thinking among professionals supports flexible, preference-sensitive care and offers actionable strategies to improve both efficiency and patient engagement across oncological pathways.